1999
DOI: 10.1182/blood.v94.12.4029.424k21_4029_4035
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Cytomegalovirus Disease After Autologous CD34-Selected Peripheral Blood Stem Cell Transplantation

Abstract: High-dose therapy with autologous peripheral blood stem cell (PBSC) rescue is widely used for the treatment of malignant disease. CD34 selection of PBSC has been applied as a means of reducing contamination of the graft. Although CD34 selection results in a 2 to 3 log reduction in contaminating tumor cells without significantly delaying engraftment, many other types of cells are depleted from the CD34-enriched grafts and immune reconstitution may be impaired. In the present study, 31 cytomegalovirus (CMV)-sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
2
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 34 publications
2
72
2
4
Order By: Relevance
“…40,41 Subsequently, other reports confirmed the relevance of this issue, although reporting a variable rate of incidence ranging between 30 to 40% and 1 to 13%, according to different diagnostic strategies. 5,[42][43][44][45][46][47][48][49] Even though all these studies showed a significant reactivation rate of CMV infection in patients undergoing ASCT, CMV disease was a rare event, although representing a serious life-threatening risk, with a clinical course and mortality rates similar to those observed after allo-HSCT. 1 3,7,8,39,52,[54][55][56][57][58][59] Of note, overt CMV disease incidence and mortality appear similar irrespective to the diagnostic strategy adopted, further suggesting the limited usefulness of a prospective monitoring of CMV infection.…”
Section: Cytomegalovirus Infection In Autologous Hematopoietic Stemmentioning
confidence: 99%
“…40,41 Subsequently, other reports confirmed the relevance of this issue, although reporting a variable rate of incidence ranging between 30 to 40% and 1 to 13%, according to different diagnostic strategies. 5,[42][43][44][45][46][47][48][49] Even though all these studies showed a significant reactivation rate of CMV infection in patients undergoing ASCT, CMV disease was a rare event, although representing a serious life-threatening risk, with a clinical course and mortality rates similar to those observed after allo-HSCT. 1 3,7,8,39,52,[54][55][56][57][58][59] Of note, overt CMV disease incidence and mortality appear similar irrespective to the diagnostic strategy adopted, further suggesting the limited usefulness of a prospective monitoring of CMV infection.…”
Section: Cytomegalovirus Infection In Autologous Hematopoietic Stemmentioning
confidence: 99%
“…In fact, previous observations, over the last 10-15 years, suggested an incidence of CMV reactivations, based on routine monitoring by polymerase chain reaction (PCR)/antigenemia CMV, of between 30% and 40% of subjects presenting with either lymphoma or MM. However, the incidence decreases to 1-13% when CMV determination was performed only on the basis of clinical signs pointing to a clinical suspicion of CMV infection (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In addition, most studies performed have considered single, rather than tandem, transplantation.…”
mentioning
confidence: 99%
“…7,8 This has sometimes been related to an increase in the morbidity of the procedure. 9,10 The ex vivo culture of HPCs with various combinations of cytokines can increase the number of colonyforming unit-granulocyte-macrophage (CFU-GM) and CD34+ cells. 11 In vivo studies in baboons have shown that expanded CD34+ cells can substantially reduce neutropenia after myeloablation.…”
mentioning
confidence: 99%